Rate of returns to education for secondary school techers in Bangladesh with bootstrap sampling - Huq, Molla Md. Rashidul (BRAC University, 2010)
Rate of returns to education is very important for policy makers and investors. Numerous works have been done regarding this but very few are available in the context of Bangladesh, specially addressing the teachers in Bangladesh. This paper investigates the labour market returns to education for the secondary school teachers of Bangladesh with the help of a nationwide survey. Different returns to different aspects of the determinants of labour market including teacher quality and school quality were perceived. Also bootstrap sampling method was utilized to ensure the accuracy of the results. The results may assist, in different ways, to understand the wage-education mechanism for the teachers in Bangladesh.